Immigrants, Imports, and Welfare: Evidence from Household Purchase Data - Brett A. McCully; Torsten Jaccard; Christoph Albert (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Who buys imports? By augmenting U.S. grocery purchase data to include origin countries of both products and households, we provide the first evidence that immigrants exhibit substantially stronger preferences for imported consumer goods than natives. We develop and estimate a quantitative trade model to show that immigrants also reduce trade costs and expand the effective market size for foreign goods, thereby increasing local import supply for all households. Overall, however, immigrants generate considerably more local import expenditure via their own purchases than via spillovers to natives, with profound implications for the distributional costs of a negative trade shock, such as an import tariff: the average within-county difference in welfare costs between immigrants and natives is over six times the across-county standard deviation in native household costs.
Keywords: F22; J31; J61; R11; 330; gains from trade; heterogeneous preferences; spillover effects